HOLISTIC LEARNING: THE CASE FOR RELIGIOUS EDUCATION IN SECULAR FRAMEWORKS - Javad Ahmad Mir; Iqbal Malik; Shabir Ahmad Lone (PT. Radja Intercontinental Publishing, 2025)
The incorporation of faith-based education within secular institutions remains a subject of significant debate, as it seeks to balance inclusivity and pluralism with concerns over religious neutrality. This study examines the rationale, benefits, and challenges of integrating religious education into secular settings, particularly in the context of India’s National Education Policy (NEP) 2020. Rather than fostering division, religious education contributes to ethical development, social harmony, and cultural understanding. By instilling moral values and promoting interfaith dialogue, it enhances national knowledge systems and supports holistic learning. However, challenges such as fears of indoctrination, curriculum resistance, and ensuring fair representation of diverse religious perspectives complicate its integration. The NEP 2020’s focus on value-based and multidisciplinary education provides an opportunity to incorporate religious education within a secular framework. Drawing from academic literature, government reports, and expert perspectives, this research highlights the potential of religious education to strengthen the moral and intellectual foundations of society. It also emphasizes addressing challenges through transparent policies, inclusive curriculum development, and structured teacher training. This study employs qualitative methods, including regressive analysis, to offer a comprehensive exploration of the topic.